2006
DOI: 10.1177/112070000601604s05
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes following Minimally Invasive Total Hip Arthroplasty Using a two-Incision Approach versus a Mini-Posterior Approach

Abstract: We evaluated early clinical results and radiographic findings of MIS THA using 2-incsion approach and mini-posterior approach. A consecutive series of 35 patients (40 hips) with 2-incision THA and a consecutive series of 35 patients (36 hips) with mini-posterior THA performed in the same period were evaluated. The patient groups were not randomised. At the mean follow-up of 20.2 months (range, 12-36 months), the 2-incision group had significantly earlier ambulation, driving ability and return to work. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…As depicted in Figure 3a, two studies including 148 patients reported the operative time along with SD 19,20 . The data was analysed using a random effect model due to the existence of significant heterogeneity ( P < 0.00001, I 2 = 96%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As depicted in Figure 3a, two studies including 148 patients reported the operative time along with SD 19,20 . The data was analysed using a random effect model due to the existence of significant heterogeneity ( P < 0.00001, I 2 = 96%).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the mini‐posterior THA, patients receiving the two‐incision THA suffered from reduced operative blood loss significantly (MD = 73.07, 95% CI 6.57–139.57, P = 0.03). In one included study, Tanavalee et al 19 . found that patients in the two‐incision group showed increased operative time than the mini‐posterior group (mean 55.00; 95% CI 46.43–63.57).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanavalee et al19) reported that two-incision THA required long operation time and resulted in massive blood loss. In the study by Yoon et al,11) there was no difference in the mean operation time between the conventional method and single-incision MIS, but it took 20 more minutes with two-incision MIS.…”
Section: Discussionmentioning
confidence: 99%
“…Cup dislodgment reported was a mistake of the surgeon and not a real complication of the technique as he felt self-confident with the acetabulum purchase without testing the grip of the cup. Rapid early return to function related to minimally invasive surgery (Duwelius & Dorr, 2008;Khan et al, 2006;Seng et al, 2009) has been reported in many papers but these techniques have shown increase complications, especially with the two-incision technique (Desser et al, 2010;Pagnano et al, 2005;Tanavalee et al, 2006). Mini-posterior and direct anterior approach report show rapid recovery function for patients (Duwelius & Dorr, 2008;Klausmeier et al, 2010;Lin et al, 2007;Mardones et al, 2005;Procyk, 2007;Stehlík et al, 2008) but these were limited to the early experience of a few surgeons.…”
Section: Discussionmentioning
confidence: 99%